CHALLENGES OF WESTERN BALKAN COUNTRIES IN THE PROCESS OF GLOBALIZATION THE CASE OF KOSOVO - Asllani, Gani (European Scientific Journal, ESJ, 2014)
The study paper addresses a range of issues and gives explanations regarding the definition of globalization, problems and challenges, aspects of globalization in economic development, the complexity of this process, countries in Western Balkan and the place of Kosovo in these processes of global integration and the EU. The EU integration process is a tool for strengthening and accelerating the transition process, as these processes are mutually reinforcing. The final goal of the Western Balkan countries is to transform their economies into viable market economies and to achieve integration into the European Union. EU accession is seen as crucial for a successful domestic transformation. Further progress with the EU accession process is of great importance for the continuation of institutional reforms and establishment of a functioning market economy across the Western Balkans.